An approach to the patient with a post-nasal drip and rhinosinusitis - Darlene E. Lubbe (South African Family Practice)
Post-nasal drip (PND) can be a bothersome symptom and one of the main reasons for patients visiting a general practitioner (GP), pulmonologist or ear, nose and throat (ENT) surgeon. It can be either a symptom, sometimes not appreciated by the examining practitioner, or an important clinical sign suggesting rhinosinusitis. This article aims to explain the aetiological factors and initial work-up of the patient with a PND and rhinosinusitis and suggest a treatment paradigm for practitioners.